THE COMPARISON OF READING COMPREHENSION IN NARRATIVE TEXT THROUGH PSRA AND QAR STRATEGIES - Marliani Pironikan; Yeni Anggeriani; Sri Hayati (Didascein : Journal of English Education, 2022)
The study's objectives were to determine: (1) whether or not there was any significant achievement on students' reading comprehension between students who were taught by PSRA Strategy, (2) whether or not there was any significant achievement on students' reading comprehension who were taught by QAR Strategy, and (3) whether or not there was any significant difference in students' reading comprehension achievement between students who were taught by PSRA and QAR Strategy. The population consisted of all tenth-grade students at SMA Negeri 1 Muara Payang in the academic year 2021/2022. The samples involved two groups, selected using purposive sampling, consisting of 32 students for each group. This study used a quasi-experimental design The test as data collection was given as pre-test and post-test. The findings revealed that both PSRA and QAR strategy had a significant impact on students' reading achievement in each class. Based on the data, the students' mean post-test score in the experimental group who were taught using the PSRA was 84.63 and the students' mean post-test score in the control group who were taught using the QAR was 79.70. Based on the independent sample t-test analysis, the t-obtained (3.216) was found to be greater than the t-table (1.671), indicating that there was a significant difference in students' reading comprehension achievement between those taught utilizing PSRA Strategy and those taught utilizing QAR Strategy.